Impact on hospitalizations of long-term versus short-term therapy with sodium zirconium cyclosilicate during routine outpatient care of patients with hyperkalemia: the recognize I study. (7th February 2023) - Pollack, Charles V.; Agiro, Abiy; Mu, Fan; Cook, Erin E.; Lemus Wirtz, Esteban; Young, Joshua A.; Betts, Keith A.; Brahmbhatt, Yasmin G.
ABSTRACT: Background: Hyperkalemia is associated with increased healthcare resource utilization (HRU). This study evaluated the impact of sodium zirconium cyclosilicate (SZC) use on HRU in outpatients with hyperkalemia. Research design and methods: A retrospective noncomparative study using claims data from the HealthVerity warehouse, which included outpatients in the United States who initiated SZC between January and December 2019 (index date) with ≥6 months' continuous coverage before (baseline) and after (follow-up) the index date (total coverage of 12 months). The study aimed to describe HRU with long-term and short-term SZC (defined as >90 and ≤90 days' supply, respectively, during 180 days' follow-up) and identify characteristics associated with long-term versus short-term therapy. Results: Of 1153 patients, 748 (64.9%) received short-term and 405 (35.1%) received long-term therapy. During follow-up, lower proportions of patients on long-term versus short-term therapy had hyperkalemia-related hospitalizations (10.1% vs 15.1%; P < 0.05) and all-cause hospitalizations (22.5% vs 29.3%; P < 0.05). Hyperkalemia-related and all-cause hospitalization proportions were 33.0% and 23.3% lower, respectively. Predictors of long-term therapy included stage 3 chronic kidney disease. Conclusions: Approximately one-third of patients with hyperkalemia received long-term SZC therapy. Hyperkalemia-related and all-cause hospitalization proportions were lower with long-term therapy, although further confirmatory studies are needed.